1996
DOI: 10.1002/(sici)1097-4547(19961215)46:6<734::aid-jnr10>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by neurosteroids of the in vivo (+)-[3H]SKF-10,047 binding to ?1 receptors in the mouse forebrain

Abstract: Recent reports suggest an interaction between neuro‐(active)steroids and sigma1 (σ1) receptors, affecting biochemical parameters as well as physiological responses mediated by σ1 ligands in the rodent brain. In this study, we examined the modulation by neurosteroids of the haloperidol‐sensitive in vivo (+)‐[3H]SKF‐10,047 binding to σ1 sites in the mouse hippocampus and cortex. Progesterone (PROG; 2–40 mg/kg), pregnenolone sulfate (PREGS; 10–40 mg/kg), and dehydroepiandrosterone sulfate (DHEAS; 10–40 mg/kg) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
30
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 33 publications
8
30
1
Order By: Relevance
“…In the present study, PROG at 10-50 mg/kg, which inhibit the in vivo haloperidol-sensitive [ 3 H]-(ϩ)-SKF-10,047 binding to sigma 1 receptor in the mouse hippocampus and cortex (Maurice et al 1996), had no effect on the conditioned fear stress response in mice. Like NE-100, PROG be- NEUROPSYCHOPHARMACOLOGY 2000-VOL.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In the present study, PROG at 10-50 mg/kg, which inhibit the in vivo haloperidol-sensitive [ 3 H]-(ϩ)-SKF-10,047 binding to sigma 1 receptor in the mouse hippocampus and cortex (Maurice et al 1996), had no effect on the conditioned fear stress response in mice. Like NE-100, PROG be- NEUROPSYCHOPHARMACOLOGY 2000-VOL.…”
Section: Discussionsupporting
confidence: 66%
“…Some neurosteroids such as PREGS and PROG have been shown to have an affinity for sigma 1 receptors (Su et al 1988;Walker et al 1990). Further, Maurice et al (1996) have reported that exogenous administration of neurosteroids leads to dose-dependent inhibition of in vivo binding of […”
Section: Receptor Agonist ( ϩ )-N-allylnormetazocine (( ϩ )-contrasting
confidence: 48%
See 2 more Smart Citations
“…Su and collaborators (1988) showed an inhibition of [ 3 H](+)-SKF 10,047 binding in the guinea-pig brain and of [ 3 H]-haloperidol in the spleen by progesterone with Ki values in the nanomolar range. Other steroids, such as testosterone, pregnenolone sulfate, or deoxycorticosterone, exhibit Ki values in the micromolar range (McCann and Su 1991;Maurice et al 1996). Confirming these studies, other groups have shown that progesterone was indeed the neurosteroid which most potently inhibited the binding of 3 Poncelet et al (1993) several sigma-1 ligands in different preparations, such as the rat brain, splenocytes plasma membrane, and liver microsomes (Ross 1991;Klein and Musacchio 1994;Yamada et al 1994).…”
Section: Endogenous Ligands Of the Sigma Receptorsmentioning
confidence: 89%